Applications of Air Mass Trajectories. (1st March 2015) - Pérez, Isidro A.; Artuso, Florinda; Mahmud, Mastura; Kulshrestha, Umesh; Sánchez, M. Luisa; García, M. Ángeles
Abstract : Air trajectory calculations are commonly found in a variety of atmospheric analyses. However, most of reported research usually focuses upon the transport of pollutants via trajectory routes and not on the trajectory itself. This paper explores the major areas of research in which air trajectory analyses are applied with an effort to gain deeper insights into the key points which highlight the necessity of such analyses. Ranging from meteorological applications to their links with living beings, air trajectory calculations become important tool especially when alternative procedures do not seem possible. This review covers the reports published during last few years illustrating the geographical distribution of trajectory applications and highlighting the regions where trajectory application research proves most active and useful. As a result, relatively unexplored areas such as microorganism transport are also included, suggesting the possible ways in which successful use of air trajectory research should be extended.